Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1097/00007890-200107270-00018
|View full text |Cite
|
Sign up to set email alerts
|

Posttransplant Immune Hepatitis in Pediatric Liver Transplant Recipients: Incidence and Maintenance Therapy With Azathioprine

Abstract: A total of 2.35% of our transplant children present evidence of immune hepatitis after transplantation. Patients do not respond to increasing cyclosporine or tacrolimus levels and require steroid and azathioprine. In view of this specific treatment, systematic screening for "autoimmune" markers is advised in children with liver transplant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
104
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(111 citation statements)
references
References 16 publications
6
104
0
Order By: Relevance
“…However, in univariate analysis there was not a significant difference in the development of d-AIH and primary immunosuppressant (Table 3, p = 0.40). Previous studies have shown variability in the type of primary immunosuppression and the development of d-AIH (3)(4)(5)(6)(7)(8). One of the weaknesses of a retrospective study such as ours is that while it may demonstrate associations, it does not lend itself well toward evaluating the role that one medication versus another may play in the development of d-AIH.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…However, in univariate analysis there was not a significant difference in the development of d-AIH and primary immunosuppressant (Table 3, p = 0.40). Previous studies have shown variability in the type of primary immunosuppression and the development of d-AIH (3)(4)(5)(6)(7)(8). One of the weaknesses of a retrospective study such as ours is that while it may demonstrate associations, it does not lend itself well toward evaluating the role that one medication versus another may play in the development of d-AIH.…”
Section: Discussionmentioning
confidence: 76%
“…In the series by Gupta et al all patients were on low-dose monotherapy calcineurin inhibitors at the time of d-AIH diagnosis, which the authors speculate may have triggered d-AIH (6). On the contrary, Andries et al reported that prior to the diagnosis of d-AIH 10 of 11 patients required daily prednisone to keep their LFTs within normal limits (4). Such variability highlights differences in management of immunosuppression from center to center.…”
Section: Venick Et Almentioning
confidence: 99%
See 2 more Smart Citations
“…1 Occasional examples of de novo autoimmune-like hepatitis have been reported following liver, bone marrow or stem cell transplantation. [3][4][5][6][7][8] Other etiologies including viral hepatitis, non-alcoholic steatohepatitis and metabolic liver disease were excluded. The diagnosis was distinguished from chronic GVHD as liver histopathology did not reveal any changes consistent with GVHD (Table 2).…”
mentioning
confidence: 99%